Fatigue-induced change in corticospinal drive to back muscles in elite rowers - Fulton, R. C.; Strutton, P. H.; McGregor, A. H.; Davey, N. J. (The Journal of Physiology, 2002)
Following exercise, motor evoked potentials (MEPs) produced in response to transcranial magnetic stimulation (TMS) of the motor cortex show a brief initial increase in amplitude followed by a longer depression in amplitude (Samii et al. 1996). Similar studies examining H-reflexes suggested that these fatigue-driven changes in MEP amplitudes are likely to be of central origin (Brasil-Neto et al. 1994). In this study we have examined post-exercise facilitation and depression in the back muscles of elite rowers and control subjects. With local ethical approval and informed consent five elite rowers with at least 5 years rowing experience at national or international level were recruited from the Imperial College Boat Club and compared with six non-rowers (ages 21-23 years, all male). Subjects performed two exercise protocols on different days on a rowing ergometer (Concept IIb). Light exercise involved comfortable rowing for 10 min to maintain a subject-weight-adjusted workload and firm exercise involved rowing as fast as possible for 1 min. Surface electromyographic (EMG) recordings were made bilaterally from erector spinae (ES) muscles at the L3/L4 level and from the first dorsal interosseus (1DI) muscle of the dominant hand. TMS was applied using a MagStim 200 stimulator and an angled double-cone stimulating coil with its cross-over located over the vertex with the induced current flowing in a posterior to anterior direction. Stimulation strength was set to 1.2 X threshold in relaxed ES muscles. Ten MEPs were recorded from all three muscles in a trial before exercise and in further trials at 2 min intervals post-exercise. The non-rowers showed a brief facilitation of MEPs in ES 2 min after light and firm exercise, which was absent in the rowers after light exercise. In the period 4-16 min after light exercise, the mean (± S.E.M.) MEP amplitude, relative to pre-exercise levels, was larger (Student's t test, P < 0.05) in the rowers (79.4 ± 2.1 %) than in the non-rowers (60.9 ± 2.5 %) in the left ES but not significantly so in the right ES (P = 0.067). Mean MEP amplitudes in 1DI were larger (P < 0.05) in the rowers, averaging 119.0 ± 3.1 % pre-exercise levels, compared with 101.2 ± 5.8 % in the non-rowers. Latencies of MEPs after light exercise were longer in all three muscles in the rowers than in the non-rowers (P < 0.05). There were no differences in MEP depression or latency between rowers and non-rowers after firm exercise. We conclude that the smaller degree of MEP depression in the rowers after light exercise reflects less central fatigue within corticospinal control pathways than that seen in the non-rowers. The longer latency of MEPs seen in the rowers may reflect recruitment of more slower-conducting fatigue-resistant motor units compared with the non-rowers. These differences may be because the energy requirements for the non-rowers during light exercise are closer to their maximum capacity leading to more fatigue. This notion is supported by the lack of any difference between groups following firm exercise when both groups were working at their maximum.